The Lower to middle Jurassic of the Maláguide complex (Internal Zones, Betic Cordillera, S Spain) in Sierra Cabrera (Almería) and Cerro de San Antón (Málaga) - Juan C. Braga; Fernando Sola; María José Comas-Rengifo; Davide Bassi (Journal of Iberian Geology, 2025)
The lithostratigraphy, age and paleoenvironmental interpretation of Lower to Middle Jurassic carbonates in Sierra Cabrera (Almería) and Cerro de San Antón (Málaga city) add to the knowledge of the sedimentary evolution of the Maláguide Complex (Internal Zones, Betic Cordillera, southern Spain). In the Barranco de Azagador section in Sierra Cabrera, Sinemurian–Pliensbachian shallow-water carbonates show a mosaic breccia and a hardground at the top. The breccia matrix and the overlying deposits are reddish crinoid packstones with hardgrounds and ammonites late Pliensbachian in age. These features suggest an extensional breakup of an initial carbonate platform giving way to pelagic reduced sedimentation. Three overlying intervals of debris-fall breccias evidence deposition on or at the base of an escarpment. Clasts in the last breccia are Middle Jurassic oolites. In the Cerro de San Antón, shallow-water carbonates change upwards to several intervals of debris-fall breccias with clasts from underlying carbonates and a crinoid packstone matrix. Crinoid packstones with hardgrounds and late Pliensbachian-earliest Toarcian ammonites overlie the breccias. As in the Barranco de Azagador, the disintegration of the pre-late Pliensbachian carbonate platform was followed by pelagic sedimentation on or at the foot of an escarpment. The crinoid packstone is brecciated and covered with a red sandstone that also fills the spaces of laterally equivalent breccias, indicating emersion. Marine sedimentation was regained in the Middle Jurassic with ooid grainstones formed in shoals. The sedimentary evolution of both sections reflects the Pliensbachian rifting phase recognised in other areas of the Maláguide Complex, although the later evolution differs in the two study outcrops.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Non-cholera Vibrio spp. invasive infections in the summer following May 2023 flood disaster in Romagna, Italy: a case series - I. Zaghi; G. Tebano; E. Vanino; G. Vandi; M. Cricca; V. Sambri; M. Fantini; F. Di Antonio; M. Terzitta; E. Russo; F. Cristini; P. Bassi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Prevalence and Risk Factors Associated With Natural Infection by Trypanosoma evansi in Campeiro Horses - Lisiane Golombieski; Gabriela Bassi das Neves; Mariana da Silva Casa; Gabriela Campos de Souza Costa; Luiz C. Miletti; Mere E. Saito; Joandes H. Fonteque (Journal of Equine Veterinary Science, 2023)

Proposal of a reliable scoring system for the histological assessment of multiorgan injury in large animal models of ischaemia and shock - C. Palmieri; L. See Hoe; W. Dyer; S. Heinsar; S. Rozencwaig; J.P. Tung; N. Bartnikowski; M. Passmore; M. Bouquet; K. Hislop; E. Wilson; g. Li Bassi; et al. (Journal of Comparative Pathology, 2023)

Postmortem analysis of WWI human remains from Italian glaciers in rare environmental conditions - Daniel Gaudio; L. De Luca; V. Cirielli; M. Caccianiga; C. Bassi; N. Cappellozza; A. Galassi; F. Nicolis; C. Cattaneo (Archaeological and Anthropological Sciences, 2019)

Plant invasions on small Mediterranean islands: An overview - L. Celesti-Grapow; L. Bassi; G. Brundu; I. Camarda; E. Carli; G. D’Auria; E. Del Guacchio; G. Domina; G. Ferretti; B. Foggi; L. Lazzaro; P. Mazzola; et al. (Plant Biosystems, 2016)

Spinal GABA-B receptor modulates neutrophil recruitment to the knee joint in zymosan-induced arthritis - Gabriel S. Bassi; David do C. Malvar; Thiago M. Cunha; Fernando Q. Cunha; Alexandre Kanashiro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Radiation hybrid QTL mapping of Tdes2 involved in the first meiotic division of wheat - F. M. Bassi; A. Kumar; Q. Zhang; E. Paux; E. Huttner; A. Kilian; R. Dizon; C. Feuillet; S. S. Xu; S. F. Kianian (Theoretical and Applied Genetics, 2013)

Development of COS-SNP and HRM markers for high-throughput and reliable haplotype-based detection of Lr14a in durum wheat (Triticum durum Desf.) - Irma Terracciano; Marco Maccaferri; Filippo Bassi; Paola Mantovani; Maria C. Sanguineti; Silvio Salvi; Hana Šimková; Jaroslav Doležel; Andrea Massi; Karim Ammar; James Kolmer; Roberto Tuberosa (Theoretical and Applied Genetics, 2013)

Improvement of biomolecular methods for the identification and typing of Escherichia coli O157:H7 isolated from raw meat - A. Paris; S. Bonardi; C. Bacci; E. Boni; F. Salmi; L. Bassi; F. Brindani (Veterinary Research Communications, 2010)

The maximum age of Hawaiian terrestrial lineages: geological constraints from Kōko Seamount - David A. Clague; Juan C. Braga; Davide Bassi; Paul D. Fullagar; Willem Renema; Jody M. Webster (Journal of Biogeography, 2010)
Aim To determine if Kōko Seamount submerged below sea level before Kure Island and Pearl and Hermes Reef formed, resulting in a period in which there were no extant islands. A period with no islands would eliminate prior terrestrial and shallow marine biotas that could migrate from island to island and require a restart of colonization from distant shores to populate the younger islands of the Hawaiian volcanic chain. Location Emperor Seamount Chain, north‐central Pacific Ocean. Methods We estimate subsidence rates for Kōko Seamount using ages determined from fossil large foraminifera and Sr‐isotopes, and maximum depths using palaeodepth estimates based on coralline algae. These data are combined with palaeolatitude changes as the Pacific Plate moved northwards, sea level variations, and sea surface temperature variations at the seamount through time to reconstruct the time and causes of submergence. Results Rounded carbonate clasts include three facies: zooxanthelate corals, bioclastic packstones to rudstones, and rhodolith floatstones. Two rudstones contain relatively deep‐water, coralline algal rhodoliths and large foraminifera indicative of Aquitanian (20.4–20 Ma) and Burdigalian (20–16 Ma) stages of the Early Miocene, consistent with Sr‐isotope ages of algae and one sample of large foraminifera. Corals grew on Kōko Seamount from c . 50 to 27.1 ± 0.4 Ma, the youngest Sr‐isotope age of a coral sample. These shallow, warm‐water coral reefs came under increasing stress as the volcano subsided at 0.012 ± 0.003 mm yr −1 , and migrated northwards, and as global climate cooled. The summit submerged and shallow coral reef growth ceased before 29 Ma, probably around 33 Ma. The volcano continued its slow subsidence, and deep‐water carbonates accumulated until they too were unable to keep pace, dying out at c . 16 Ma. Main conclusions The final submergence of the summit of Kōko Seamount by about 33 Ma confirms that biota on older Hawaiian–Emperor Islands could not have migrated from island to island along the entire chain to eventually colonize the present Hawaiian Islands. There was a period between at least 33 and 29 Ma in which no islands existed, and distant colonization had to repopulate the younger portion of the Hawaiian chain, which began to emerge between about 29 and 23 Ma.

Occurrence of TRGV-BJ hybrid gene in SV40-transformed fibroblast cell lines - L. P. G. D’Arce; C. L. Bassi; A. L. Fachin; G. A. S. Passos; E. T. Sakamoto-Hojo (Genetica, 2009)

Evidence for mediation of nociception by injection of the NK-3 receptor agonist, senktide, into the dorsal periaqueductal gray of rats - Gabriel S. Bassi; Ana C. Broiz; Margarete Z. Gomes; Marcus L. Brandão (Psychopharmacology, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Photosynthesis research in Italy: a review - Giorgio Forti; Angela Agostiano; Roberto Barbato; Roberto Bassi; Enrico Brugnoli; Giovanni Finazzi; Flavio M. Garlaschi; Robert C. Jennings; Bruno Andrea Melandri; Massimo Trotta; Giovanni Venturoli; Giuliana Zanetti; et al. (Photosynthesis Research, 2006)

A Zea mays 39-kDa thylakoid transglutaminase catalyses the modification by polyamines of light-harvesting complexII in a light-dependent way - M. Della Mea; A. Di Sandro; L. Dondini; S. Del Duca; F. Vantini; C. Bergamini; R. Bassi; D. Serafini-Fracassini (Planta, 2004)

Occurrence of the lutein-epoxide cycle in mistletoes of the Loranthaceae and Viscaceae - Shizue Matsubara; Tomas Morosinotto; Roberto Bassi; Anna-Luise Christian; Elke Fischer-Schliebs; Ulrich Lttge; Birgit Orthen; Augusto C. Franco; Fabio R. Scarano; Britta Frster; Barry J. Pogson; C. Barry Osmond (Planta, 2003)

The structure of duplications on human acrocentric chromosome short arms derived by the analysis of 15p - I. Piccini; L. Ballarati; C. Bassi; M. Rocchi; A. Marozzi; E. Ginelli; R. Meneveri (Human Genetics, 2001)

Influence of River Water in the Detection of Cr(VI) Mutagenicity by the Ames Test - L. C. López; M. D. Bassi; J. Moretton (Bulletin of Environmental Contamination and Toxicology, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)